The research of the non-financial factors in the investment decision - HOU, Wenbiao (Institutional Knowledge at Singapore Management University, 2024)
Driven by globalization and technological innovation, the complexity of investment decisions is continuously increasing. While traditional financial factors still play a crucial role in these decisions, an increasing number of real-life cases indicate that investors are relying more on non-financial factors. This paper systematically analyzes the impact of these non-financial factors in the framework of investment decision-making. This paper employs a mixed research method, incorporating both qualitative and quantitative analyses to ensure comprehensive coverage of the topic. First, it outlines the theoretical basis and development of non-financial factors in investment decisions through a review of prior literature. Next, it collects and analyzes a large amount of data on investor behavior and investment decision-making processes using interviews, questionnaire surveys, and empirical analyses. The main findings are as follows: 1) Protective clauses in investment contracts can reduce investment risks and enhance investor confidence, while the role of earn-out clauses is mixed; 2) Investors pay close attention to an excellent management team and a high-quality industry track, which improve investment returns and reduce investment risks; and 3) Social relationships and investment synergy effects are crucial for investment decisions, as they help reduce information asymmetry and transaction costs. These findings highlight the central role of non-financial factors in investment decisions and provide investors with a new dimension for decision-making. This paper supplements theoretical research in the field of investment decision-making by proposing a new theoretical framework for incorporating non-financial factors into investment decisions. By integrating theories on contract, management team, industry track, social relationships, and investment synergy effects, it provides investors with a multi-dimensional analytical tool to assist them in making more informed decisions in a complex environment. By identifying and quantifying non-financial factors, investors can more effectively manage investment risks, optimize investment portfolios, and enhance investment returns. In summary, the findings of this paper on the importance of non-financial factors in investment decisions offer significant theoretical and practical contributions.